Personality Goes a Long a Way: An Interhemispheric Connectivity Study - Hoppenbrouwers, Sylco S.; Farzan, Faranak; Barr, Mera S.; Voineskos, Aristotle; Schutter, Dennis J.; Fitzgerald, Paul; Daskalakis, Zafiris J. (Frontiers in Psychiatry, 2010)
Throughout the development of psychology the delineation of personality has played a central role. Together with the NEO-PI-R, a questionnaire derived from the Five Factor Model of Personality, and recent advances in research technology it is now possible to investigate the relationship between personality features and neurophysiological brain processes. The NEO-FFI, the short version of the NEO-PI-R, reliably measures five main personality traits: Neuroticism, Extraversion, Openness to experience, Agreeableness and Conscientiousness. As behaviour and some psychiatric disorders have been related to interhemispheric connectivity, the present study used the combination of transcranial magnetic stimulation (TMS) and electroencephalography (EEG) to measure frontal interhemispheric connectivity and its association with personality as indexed by the NEO-FFI. Results demonstrated that prefrontal interhemispheric connectivity between the left and right dorsolateral prefrontal cortex (DLPFC) correlates with Agreeableness in healthy subjects. This is the first study to relate personality features to interhemispheric connectivity through TMS-EEG and suggests that Agreeableness relates to the effectiveness of prefrontal communication between hemispheres.